Developing an intervention to improve the quality of childcare centers in resource-poor urban settings: a mixed methods study in Nairobi, Kenya - Oloo, Linda; Elsey, Helen; Abboah-Offei, Mary; Kiyeng, Martin; Amboka, Patrick; Okelo, Kenneth; Kitsao-Wekulo, Patricia; Kimani-Murage, Elizabeth; Langa't, Nelson; Nampijja, Margaret (Frontiers in Public Health, 2023)
Background: Globally, 350 million under-5s do not have adequate childcare. This damages their health and development and undermines societal and economic development. Rapid urbanisation is changing patterns of work, social structures and gender norms. Most mothers, work long hours for insecure daily wages. To respond to this demand, childcare centres have mushroomed in informal settlements with inadequate support to ensure they provide safe, nurturing care accessible to low-income families. We present the process of co-designing an intervention, delivered by local government community health teams to improve the quality of childcare centres and ultimately the health and development of under-5 children in informal settlements in Kenya. Methods: This mixed methods study started with a rapid mapping of the location and basic characteristics of all child-care centres in Korogocho and Viwandani informal settlements in Nairobi. Qualitative interviews were conducted with parents and grandparents (n=44), childcare providers and community health teams (n=44). A series of 7 co-design workshops with government, NGO, community health teams and childcare providers were held to design the intervention. Questionnaires to assess knowledge, attitudes and practice of community health volunteers (n=22) and childcare centre providers (n=66) were conducted. Results: In total 129 childcare centres were identified, 55 in Korogocho and 77 in Viwandani. School based providers dominated in Korogocho (73%) and home-based centres in Viwandani (53%). All centres reported minimal support from any organisation (19% supported) and this was particularly low among home-based (9%) and centre-based (14%) providers. Home-based centre providers were the least likely to be trained in early childhood development (20%), hence the co-designed intervention focused on supporting these centres. All co-design stakeholders agreed that, with further training, community health volunteers were well placed to support these informal centres. Findings showed that support to strengthening management within the centres in addition to the core domains of WHO’s Nurturing Care Framework needed to be a key component of the intervention. Conclusions: Implementing a co-design process embedded within existing community health systems and drawing on the lived-experience of childcare providers and parents in informal settlements enabled the development of an intervention with the potential to be scalable and sustainable.